2004
DOI: 10.1016/j.jallcom.2004.04.132
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of titanium–hydrogen solid solution

Abstract: The mechanical properties of titanium-hydrogen solid solution (0-7.84 at.% H) were studied to reveal the influence of hydrogen on the characteristics of titanium. The elastic moduli such as Young's and shear moduli of titanium-hydrogen solid solution decreased with increasing of hydrogen content. The influence of hydrogen content for decreasing of elastic moduli was independent of temperature. The microhardness for the solid solution was also decreased with increasing of hydrogen content. The electronic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…(7) was equal to the number of all atoms in the unit cell. In this figure, the authors re-calculated the Debye temperature as 375 K assuming that N is 4, for comparing with the results of the present study, and for the unification with our previous studies [12][13][14]. The Debye temperature of the hydride is more than twice as large as that of the metal and increases with hydrogen addition.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…(7) was equal to the number of all atoms in the unit cell. In this figure, the authors re-calculated the Debye temperature as 375 K assuming that N is 4, for comparing with the results of the present study, and for the unification with our previous studies [12][13][14]. The Debye temperature of the hydride is more than twice as large as that of the metal and increases with hydrogen addition.…”
Section: Resultssupporting
confidence: 71%
“…The H V /E for the ␦-YH 2−x is 0.0275, which is a middle value between metal and ceramics. Since this ratio is larger than the ratio for ␦ TiH 2−x [14] or ␦ ZrH 2−x [12,13], the yttrium hydride has different deformation mechanism from IV-metal hydrides, the reason of which is that the dependency of hydrogen for the mechanical properties of yttrium hydride is different from the zirconium hydride or titanium hydride. For further discussion, a molecular orbital calculation or experiments for other metal hydrides will be required, which are now in progress.…”
Section: Resultsmentioning
confidence: 88%
“…Atomic hydrogen originating from the CVD diamond coating process can lead to fast hydrogenation of substrates due to the fact that hydrogen easily diffuses into titanium metal. So, titanium base materials are sensitive to the influence of hydrogen and temperature [12]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the difficulties, the poor adhesion, due to diamond/titanium mismatch and the difference of the thermal expansion coefficients between diamond and Ti may be highlighted. Besides, the rapid in-diffusion of light elements forming non-diamond species promotes the hydrides formation which cause a degradation of the mechanical properties of the Ti substrates [12,13]. However an interfacial TiC layer may minimize the residual thermal stress between substrate and the diamond film.…”
Section: Introductionmentioning
confidence: 99%
“…Although the properties on thin film of yttrium metal or yttrium hydride have been published [1][2][3][4], there is inadequate information on yttrium hydrogen solid solution and yttrium hydride for the bulk samples. In the previous works, the authors found that the solute hydrogen deteriorates the mechanical strength of zirconium hydrogen solid solutions [5] and titanium hydrogen solid solutions [6].…”
Section: Introductionmentioning
confidence: 97%